Isolation, identification and characterization of Morganella morganii from Naja naja atra in Beijing, China - Wang, H-F.; Du, L-Y.; Luo, J.; He, H-X. (Cellular and Molecular Biology, 2017)
Morganella morganii is an important opportunistic human pathogen and belongs to the family of Enterobacteriaceae. Although it is widely distribution, it only be considered a rare cause of human infections. We report the isolate of M. morganii from Naja naja atra following infections of heart, lung and liver. Seven strains were confirmed using 16S rDNA amplified and sequences. Antimicrobial susceptibility testing of M. morganii isolates demonstrated ubiquitous resistance to ampicillin, amoxicillin/clavulanic acid, cefazolin, cephalothin, sulfamethoxazole/trimethoprim, sulfamethoxazole et al. However, M. morganii ubiquitous susceptible to piperacillin, ampicillin/sulbactam, piperacillin/tazobactam, cefixime et al. Further investigate display gyr B and Sul2 genes presence in all M. morganii isolates. AAC(3)-II was found in E2, E3 and E6 M. morganii. gyrA and qnrB expression in M3 and M6 M. morganii. This is the first description in M. morganii carrying AAC(3)-II, gyrB, gyrA, qnrB, and Sul2 genes from Naja naja atra, which suggests the increasing risk of pathogen transmission between humans and wildlife.